Recent results from Pb-Au collisions at 158 GeV/c per nucleon obtained with the CERES spectrometer - Agakishiev, Geydar; Appelshäuser, Harald; Braun-Munzinger, Peter; Esumi, ShinIchi; Glässel, Peter; Lenkeit, Björn; Messer, Matthias; Richter, Michael; Seipp, Wolfram; Specht, Hans Joachim; Stachel, Johanna; Wessels, Johannes P.; et al. (Nuclear physics. A, Nuclear and hadronic physics, 1999)
During the 1996 lead run time, CERES has accumulated 42 million events, corresponding to a factor of 5 more statistics than in 1995 and 2.5 million events of a special photon-run. We report on the results of the low-mass e+e−-pair analysis. Since the most critical item is the poor signal-to-background ratio we also discuss the understanding of this background, in absolute terms, with the help of a detailed Monte Carlo simulation. We show preliminary results of the photon analysis and summarize the results of the hadron analysis preliminarily reported on already at QM'97 [1].